Mastoid Obliteration with Autologous Bone in Mastoidectomy Canal Wall Down Surgery: a Literature Overview - Alves,Ricardo Dourado (2016)
Introduction The objectives of mastoidectomy in cholesteatoma are a disease-free and dry ear, the prevention of recurrent disease, and the maintenance of hearing or the possibility to reconstruct an affected hearing mechanism. Canal wall down mastoidectomy has been traditionally used to achieve those goals with greater or lesser degrees of success. However, canal wall down is an aggressive approach, as it involves creating an open cavity and changing the anatomy and physiology of themiddle ear andmastoid. A canal wall up technique eliminates the need to destroy the middle ear and mastoid, but is associated with a higher rate of residual cholesteatoma. The obliteration technics arise as an effort to avoid the disadvantages of both techniques. Objectives Evaluate the effectiveness of the mastoid obliteration with autologous bone in mastoidectomy surgery with canal wall down for chronic otitis, with or without cholesteatoma. Data Synthesis We analyzed nine studies of case series comprehending similar surgery techniques on 1017 total cases of operated ears in both adults and children, with at least 12 months follow-up. Conclusion Mastoid Obliteration with autologous bone has been utilized for many years to present date, and it seems to be safe, low-cost, with low recurrence rates - similar to traditional canal wall down procedures and with greater water resistance and quality of life improvements.